2022
DOI: 10.3390/en15218084
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Micro Gas Turbines in Energy Transition

Abstract: In the progressively rising decentralized energy market, micro gas turbines (MGT) are seen with great potential owing to their low emissions, fuel flexibility, and low maintenance. The current transformation in the landscape of electricity supply with an increasing share of fluctuant renewable energy resources and increasing complexity requires a reliable and energy-efficient power generation source to support the grid. In this scenario, small-scale power plants that are constructed based on micro gas turbines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 47 publications
(69 reference statements)
1
0
0
Order By: Relevance
“…Based on thermodynamic simulation data, the overall efficiency of the COGES system was calculated using Equation (5), resulting in a maximum efficiency of the system is 30.1%. This aligns with the practical operation of low-power-range power plants, where efficiencies typically range from 25% to 35% [54,55]. From these results, the COGES designed propulsion system can produce greater output power than commonly used factory engines such as diesel engines or dualfuel engines.…”
Section: Performance Of Coges Systemsupporting
confidence: 53%
“…Based on thermodynamic simulation data, the overall efficiency of the COGES system was calculated using Equation (5), resulting in a maximum efficiency of the system is 30.1%. This aligns with the practical operation of low-power-range power plants, where efficiencies typically range from 25% to 35% [54,55]. From these results, the COGES designed propulsion system can produce greater output power than commonly used factory engines such as diesel engines or dualfuel engines.…”
Section: Performance Of Coges Systemsupporting
confidence: 53%
“…The study recognizes the absence of effective adaptive speed control mechanisms in these countries, where limited resources, unreliable power grids, and harsh environmental conditions pose major obstacles to ensuring optimal functionality. In addition, [7][9][28] [4] studied the use of MGTs in cogeneration applications for heat production. Here, this research paper seeks to contribute to the field of evolutionary-inspired adaptive speed control for MGT-based systems using genetically optimized solutions.…”
Section: Identified Research Gapmentioning
confidence: 99%
“…Notably, MGTs are widely used in various applications [4], including distributed power generation, cogeneration, and hybrid electric vehicles. They require precise speed control to ensure optimal performance and efficiency [8].…”
mentioning
confidence: 99%
“…This paper also discusses how micro-gas turbines could be integrated with other energy systems such as Energies 2024, 17, 873 2 of 21 solar fields, ORCs, and fuel cells. Banihabib and Assadi [2] acknowledged the growing significance of micro-gas turbines in the expanding market of decentralized energy, citing advantages like low emissions, versatility in fuel use, and minimal maintenance requirements. They also addressed the need to enhance the operational adaptability, dependability, and availability of these turbines while still minimizing environmental impact.…”
Section: Introductionmentioning
confidence: 99%
“…Miki et al [7] used the Open National Combustion Code to simulate a 1/15 sector of a realistic combustor and first-stage high-pressure turbine. They performed three different cases: (1) without the vane and (2,3) with the vane at different clocking conditions. They found that the presence of the vane caused a noticeable difference in the flowfield.…”
Section: Introductionmentioning
confidence: 99%